Sistema web para la gestión médica del área de salud 2 de Quevedo - Petao Tubay, Milton Armando (2015)
This work called "web system for the medical management of the Health Area 2 of Quevedo," arises from the need to optimize and improve their safety and flexibility to manipulate the information in the statistics department of the Health Area 2 Quevedo. The staff in charge of this area meets a responsibility to keep an accurate record control and medical history of the patients, who are treated in this hospital, however this work has been tedious due to the amount of information every day increases, making this control a very complex task. For this reason, the creation of a web system for medical management which is oriented online management information processed in this hospital entity to facilitate and expedite the control of information was raised. This web system has been developed using the following tools: Microsoft Visual Studio C # 2008 and SQL Server Database 2008. The work was developed using the methodology of Web application development DUM; the work was structured according to the phases and characteristics of the methodology in question. Once completed the system development, the respective testing program, which has the following functions are performed: Login management, system security, user management, permission management by user type, employee management, patient management, medical management, medical management agenda operating unit management, product management, recipe management, management medical history management type of treatment. In summary this web system, allow system users to keep an accurate record of patients seen in the Health Area 2 of Quevedo